Catastrophe Containment And Relief Trust-Approval Of Grant Assistance For Debt Service Relief. (Policy Papers; Policy Paper ;, 2020)
This paper proposes that the Executive Board determine that the global COVID-19 pandemic constitutes a Qualifying Public Health Disaster (QPHD) under the Catastrophe Containment (CC) Window of the Catastrophe Containment and Relief Trust (CCRT), in line with the new QPHD test approved by the Board on March 26. The CCRT has sufficient financial resources for an initial tranche of grant assistance for debt service relief covering eligible debt falling due from all CCRT-eligible members through October 13, 2020. Fundraising efforts continue to secure the financial resources needed to commit future such tranches for CCRT debt service relief, up to a cap of two years. Staff considers that the 25 members requesting CCRT assistance qualify for immediate CCRT relief.